Cortical and subcortical brain atrophy in Parkinson's disease with visual hallucination. Issue 12 (21st October 2013) - Watanabe, Hirohisa; Senda, Jo; Kato, Shigenori; Ito, Mizuki; Atsuta, Naoki; Hara, Kazuhiro; Tsuboi, Takashi; Katsuno, Masahisa; Nakamura, Tomohiko; Hirayama, Masaaki; Adachi, Hiroaki; Naganawa, Shinji; et al.
ABSTRACT Background The aim of this study was to investigate the cortical and subcortical brain structures in Parkinson's disease (PD) with visual hallucination (VH), and to elucidate the association between the proposed hypothesis of VH in PD and regional brain volume changes. Methods We used 3T magnetic resonance imaging (MRI) and voxel‐based morphometry (VBM) to investigate the brain structures of PD patients with VH (PD‐VH; n = 13) and PD patients without VH (PD‐C; n = 13). Results The PD‐VH patients showed significant cortical atrophy compared to the PD‐C patients in the bilateral dorsolateral prefrontal cortex, left rostral region of the prefrontal cortex, left ventral section of the cingulate cortex, bilateral primary visual cortex, and secondary visual cortex including the left inferior occipital gyrus, right lingual cortex, right supramarginal gyrus, and left fusiform gyrus. Significant subcortical atrophic changes were observed in the white matter of the right parahippocampal gyrus, the bilateral posterior part of the cingulate gyrus, the left lingual gyrus, and the right middle occipital gyrus. Conclusions VH in PD can occur due to distinctive neuroanatomical involvement. © 2013 International Parkinson and Movement Disorder Society